Evaluation of a web-based registry of inherited bleeding disorders: a descriptive study of the Brazilian experience with HEMOVIDAweb Coagulopatias. Issue 1 (December 2017) - Rezende, Suely; Rodrigues, Silvia; Brito, Kelly; da Silva, Diego; Santo, Marcos; Simões, Bárbara; Genovez, Guilherme; Melo, Helder; Araújo, João; Barca, Danila
Abstract Background Inherited bleeding disorders (IBD) consist of a group of rare heterogeneous diseases, which require treatment for life. Management of these disorders is complex and costly. Therefore, good quality data of the affected population is crucial to guide policy planning. The aim of this manuscript is to describe the impact of a national, web-based registry – the Hemovidaweb Coagulopatias (HWC) – in the management of the IBD in Brazil. Methods The system was developed in PHP 5.0 language and is available on the internet athttp://coagulopatiasweb.datasus.gov.br . The system was validated in September 2008 and launched nationally with input from January 1, 2009. HWC collects variables related to socio-demographic, clinical, laboratory and treatment data of patients with IBD. Results Within 7 years, there was an increment of 90.8% on the diagnosis of IBD altogether, which increased from 11, 040 in December 2007 to 21, 066 in December 2014. This is now the fourth and third largest world population of patients with haemophilia and von Willebrand's disease (vWD), respectively, according to the most recent (2015) Annual Global Survey of the World Federation of Hemophilia. The data collected provided the basis for planning and implementing home therapy, prophylaxis and immune tolerance induction (ITI), recently initiated in Brazil. Conclusion HWC was an effective tool in the increment of registration of patients with IBD in Brazil. Furthermore, it was essential to support policy planning, monitoring, evaluation and treatment. Future development should focus on surveillance, health outcomes and research. Every country should implement a national registry on IBD.